Implementasi Penyelesaian Sengketa Industrial Dalam Perspektif Bipartit Menurut Undang-undang Nomor 2 Tahun 2004 Tentang Penyelesaian Perselisihan Hubungan Industrial - Satrya Yudha Prabawa; Sulaiman (As-Shahifah : Journal of Constitutional Law and Governance, 2023)
Abstract In the process of resolving industrial relations disputes, there are two steps that can be taken,namely through litigation and non-litigation (court or out of court), based on Law Number 2 of 2004 concerning industrial relations dispute settlement. It is part of the steps for resolving industrial disputes outside the court (non-litigation) through bipartite negotiations. The bipartite negotiation pathway is an obligation for workers (laborers) and employers to be able to do it when there are disputes or differences of opinion that have the potential to cause impacts and conflicts in industrial relations. Based on the provisions contained in Article 2 of Law Number 2 of 2004, it describes the types of industrial relations disputes including; first; rights dispute, second; conflict of interest, third; layoff disputes, and fourth; disputes between trade unions/labor unions in a particular company. Thus the implementation of the settlement through non-litigation steps with bipartite efforts can be carried out within the period determined by law, namely, no later than 30 (thirty) working days from the start of the bipartite negotiations, then based on Article 6 paragraph 2 of the Law number 2 of 2004 states that every negotiation that takes place must be recorded or the results of bipartite negotiations must be recorded. The approach used in this study uses normative and empirical legal approaches, based on this method researchers can clearly know and study doctrinal laws and the implementation of laws applied in society. thus researchers in providing views or ideas in solving legal problems that occur in society.